1996
DOI: 10.1055/s-2006-957887
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phospholipase Cγ1 Activity by Amentoflavone Isolated fromSelaginella tamariscina

Abstract: Amentoflavone was isolated as an inhibitor of phospholipase C gamma 1 (PLC gamma 1) and phosphoinositides (PI)-turnover in PLC gamma 1 overexpressing NIH3T3 fibroblasts (NIH3T3 gamma 1) from Selaginella tamariscina (Selaginellaceae) together with other related biflavonoids, isocryptomerin and cryptomerin B. Only amentoflavone inhibited the PLC gamma 1 activity with an IC50 of 29 microM and the formation of total inositol phosphates (IPt) in PDGF-stimulated NIH3T3 gamma 1 with an IC50 of 9.2 microM but did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Additionally, flavonoids can inhibit some enzymes, such 0031-9422/$ -see front matter Ó 2004 Elsevier Ltd. All rights reserved. doi:10.1016/j.phytochem.2004.11.014 as cyclooxygenase, lipoxygenase and phospholipase A 2 (Lee et al, 1996;Kim et al, 1998;Saponara and Bosisio, 1998), and are also able to chelate metals, which play an important role in metal-induced free radical reactions (Deng et al, 1997). Biflavonoids are dimers of flavonoids, linked by a C-O-C or C-C bond, their biological properties include anti-inflammatory and antiarthritic activites in animals (Harborne, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flavonoids can inhibit some enzymes, such 0031-9422/$ -see front matter Ó 2004 Elsevier Ltd. All rights reserved. doi:10.1016/j.phytochem.2004.11.014 as cyclooxygenase, lipoxygenase and phospholipase A 2 (Lee et al, 1996;Kim et al, 1998;Saponara and Bosisio, 1998), and are also able to chelate metals, which play an important role in metal-induced free radical reactions (Deng et al, 1997). Biflavonoids are dimers of flavonoids, linked by a C-O-C or C-C bond, their biological properties include anti-inflammatory and antiarthritic activites in animals (Harborne, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Since the phosphorylation of IR is essential for the insulin signaling cascade, our results indicate that amentoflavone may act in the cells to enhance insulin signaling. Although there have been several reports on the biological activities of amentoflavone, [9][10][11][12] PTP1B-inhibitory activity of amentoflavone and its cellular effect in insulin signaling is reported for the first time in this study. …”
Section: Resultsmentioning
confidence: 77%
“…1). Although amentoflavone has been reported to possess various pharmacological activities such as antioxidant, 9) anti-HIV, 10) anti-phospholipase Cg1, 11) and vasorelaxant effects, 12) there has been no study with regard to its inhibitory activity against PTP1B. In this study, we investigated the inhibitory effect of amentoflavone on PTP1B and confirmed its cellular effect on IR phosphorylation.…”
mentioning
confidence: 74%
“…Several compounds, such as amentoflavone, isocryptomerin, cryptomerine B, and tamariscinoside, have been isolated from ST. 4,20,21 Amentoflavone from ST inhibits the induction of nitric oxide synthase by inhibiting nuclear factor-B activation in macrophages and the phospholipase C-␥1 activity in fibroblasts. 22,23 Lee et al 24 previously reported that treatment with 1,000 g/mL of the water extract of ST for 3 days showed significant cytotoxicity in the human leukemia cell line U937, and some organic solvent extracts of ST increased p53 gene expression and induced G1 arrest. However, under the same experimental conditions, human peripheral blood lympocytes were insensitive to the cytotocixity of ST fractions.…”
Section: Discussionmentioning
confidence: 99%